Navigating the next surge: a perspective on Egypt’s preparedness and prospects for another COVID-19 outbreak - Aliaa A. Elhosseiny; Mohamed Salama (Population Health Metrics)
Abstract The global COVID-19 pandemic has presented healthcare systems and economies with unprecedented challenges. Like many other countries, Egypt has experienced the pandemic’s multifaceted effects. As new variants continue to emerge, countries are enhancing their preparedness and response strategies in anticipation of possible future outbreaks. This review article focuses on Egypt and discusses the impact of the COVID-19 pandemic on the country’s economy. It also examines the country’s preparedness for a potential resurgence of COVID-19. Further, it explores Egypt’s vaccination campaign, discussing the progress in achieving population immunity and the potential challenges encountered. It also extends to the public health communication strategies employed by the government, investigating their efficacy in disseminating accurate information and fostering public adherence to safety measures. While recognizing progress, the article also flags possible gaps and opportunities for improvement in Egypt’s pandemic preparedness.